Effect of muyuyo gum (Cordia lutea) as a stabilizing agent and on the shelf life of orange nectar (Citrus x sinensis) - Dueñas-Rivadeneira, Alex Alberto; Vargas-Zambrano, Plinio Abelardo; Vera-Chang, Jaime Fabián; Vásquez-Cortez, Luis Humberto; Viteri-Andrade, Wilfrido Xavier; García-Mejía, Jorge Ignacio; Alvarado-Vásquez, Kerly Estefanía; Meza-Cool, Alexandra Andreina (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Muyuyo gum represents a good opportunity to replace chemical synthesis stabilizers that are widely used and bring future consequences. Therefore, the main objective of the research was to evaluate the effect of muyuyo gum (Cordia lutea) as a stabilizing agent and on the shelf life of orange nectar (Citrus X sinensis). A completely randomized experimental design of four treatments with three repeats consisting of three concentrations plus a control (T0 – 0 % T1 – 2 %, T2 – 4 % and T3 - 6%) was applied. In each of the formulations elaborated, a sensory evaluation was carried out. The variables evaluated were sweetness, acidity and general appearance, for which a hedonic scale was used. The data were processed in the statistical program InfoStat, applying the non-parametric statistics and Kruskall Wallis test at 0,05 % significance, in the turbidity test a value of 1506,66 NTU (Nephelometric Turbidity Unit) was obtained, in treatment 1 and in treatment 2 1085,33 NTU, in the results of the physical-chemical analysis the following results were obtained; a pH of 3,37, 12.65 °Brix and a titratable acidity of 0,39. The microbiological behavior was evaluated in which T2 is the one that was given as adequate within the NTE 2 337:2008 standard. It was established that the variables Sweetness, Acidity and General Appearance were within the allowed range. It is necessary to consider that T2 (4 % muyuyo) in general is the treatment that behaves best compared to T0 (control). In what corresponds to the viscosity analysis, a range of 5,23 Pa.s was obtained which is within the established range. Therefore, it is established that muyuyo gum has stabilizing and nutritional properties which make it a promising natural food input.